Contenido de los programas deportivos radiales de Quevedo y su incidencia en la formación profesional de los estudiantes de la carrera de comunicación social de la Universidad Técnica de Babahoyo Extensión Quevedo - Chanatasig Solórzano, Alexander Jefferson (2019)
The radio is by its very nature, the medium that transmits the sounds and the image of their origin, which means that the radio is the sound medium and, consequently, only one of the five senses, the ear, intervenes. in the perception of the messages issued through this medium. The present project focuses on the plant, the strategies for the sports programs of the Quevedo canton presents a quality content in each of its formats that are transmitted to the air. The regulation system and the development of information and communication. To know the final results of analysis and interpretation and selection of information, it is applied to a series of methods and strategies to obtain data according to the problematic treated of the two variables of the research project. The application of the inductive, deductive, analytical, field and synthetic bibliography along with the interview and survey techniques addressed the topics of the content of the radio programs to transmit to the listening audience the needs.